CITIZEN PARTICIPATION AND THE MANAGEMENT OF MUNICIPAL AFFAIRS IN THE COMMUNITY OF ZOGBODOMEY IN BENIN - VODOUNNON TOTIN, K. Marius; Prof HEDIBLE, SIDONI CLARISSE; AGBODOSSINDJI, David; ZINHO, ENOCK M (My University, 2023)
Citizen participation in city governance is essential to the democratic functioning of urban society. Local government is the level of government closest to residents, and it is here that many important decisions are taken that have a direct impact on residents' quality of life. The aim of this study is to analyze citizen involvement in municipal management in Zogbodomey. Data were collected through individual interviews with 350 people belonging to sociolinguistic groups. The population of Zogbodomey has a good understanding of the concept of participatory governance, highlighting citizen participation options, communication, and inclusion in the design of development action programs, mutual trust and legislation on citizen participation. For them, the idea of participation is an inclusive process for building and carrying out development actions. According to the respondents, participation offers a number of opportunities. The investigations showed that the public was partly aware of the wide range of opportunities for civic participation. These include community media, opinion forums, development associations, professional associations, etc., taking into account the traditional councils of chiefs, etc. It should also be noted that traditional chiefdoms are involved in community development in a number of ways.
Keywords: Participation; citizen; management; municipal; Zogbodomey